SUBMISSÃO E TRANSGRESSÃO: TRAJETÓRIAS DE PERSONAGENS FEMININAS NA CONSTÍSTICA DE SONIA COUTINHO - Asadczuk, Luciana (2017)
This work has the principal aim analyses the trajectory of the feminine characters in the Sonia Coutinho work and the clash that they live between “accept old papers” established by patriarchy, living submissive or live the “human vocation”, that is, live freely like social subjects. From this context, from the instauration of the patriarchal and your high predominance, your resistance in some Brazil regions in the XX and XXI centuries, I make the analysis of the difficulties, the challenges of the protagonists characters faced in the Coutinho tales, published in 1970, 1985 and 2006, respectively. Baiana and one of the most important writers of fiction of the contemporary literature, Coutinho covers the in-transition woman, breaking with the conservatory standards and inserting themselves in the society. The analysis is held from the narrative spaces, that work like a clash between the submission and the character transgression. It was observed the feminine condition in these represented times in the tales, like how the feminine character lived in these different contexts, as well as your displacement of the provincial town to Rio de Janeiro, a developed city. With the feminine focus, the analysis explores the tales Nascimento de uma mulher (1970), O último verão de Copacabana (1985) and Ovelha Negra e Amiga Loura (2006) with theoretical reference based on the concepts of Brazilian feminism scholars, the history of the woman and their trajectory, Coelho (2002), Perrot (2007), Duarte (2011), Teles (1999), Xavier (1991), among other. Also with the theoretical contribution of Del Priore (2009; 2013), Velho (1973), Teixeira Coelho Netto (1981), Leiro (2003), Beauvoir (1970), Theories of literary space, literary theory,as well as articles, theses and dissertations about the theme.